The effect of halal certification approach on performance among Small and Medium Enterprises (SMEs) in Malaysia - Baharudin Othman,; Sharufudin Md. Shaarani,; Arsiah Bahron,; Nurul Hudani Md. Nawi, (Penerbit Universiti Kebangsaan Malaysia, 2019)
This study was designed to investigate the effects of halal certification approach through several key variables. The identified variables include planning, procedures, implementation, monitoring and assurance, and commitment to improving halal food industry performance among SMEs in Malaysia. A self-administered questionnaire with closed-ended questions to measure the planning, procedure, implementing, controlling and commitment influence the organizational performance is used. The questionnaires were distributed to the committee members amongst halal Small and Medium Enterprise (SMEs) in Malaysia, in which 344 are usable for analysis. Smart PLS version 2.0 was used to analyze the relationship of each construct. The outcome of this study showed a positive relationship between halal control, the implementation of halal standards, organizational commitment and organizational performance. The study found that organizational performance is influenced by a combination of related elements in the internal organization control, including halal control, halal standard implementation and commitment which generates a high performance. This study has provided some implications on theory, model and practical implication. Halal certification approach elements should acknowledged by all parties in transforming Malaysia as a halal hub internationally.